Kritik Teologi Salafiyah Terhadap Ahli Kalam dalam Memahami Sifat-Sifat Allah - Muhammad Istiqamah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
This study aimed to examine the various interpretations of al-Mutakallimun on the attributes of Allah from the point of view of Salafiyah Theology, then the reasons behind the occurence of these interpretations as well as the Salafiyah Theological criticism against that understanding. The method used in this study was library research referring to classical and modern literature. The research conducted in this study shows that there are several Salafiyah Theological criticisms against these various interpretations of al-Mutakallimun on the attributes of Allah. Among other things, there is a fallacious perception that if one were to define the attributes of Allah in accordance with their meanings, one would fall on tasybih on those attibutes or on the consequences of those attribute. Therefore, some al-Mutakallimun find solutions in Tafwidh and Ta’wil, and claim that the two are the way to purify and glorify Allah. Besides, there is a mistake in understanding Arabic expressions according to the context.